Sustainability and the soybean supply chain in Brazil: challenges and implications through the lens of the current reality tree - Silva, Bibiana Porto da; Cassel, Ricardo Augusto; Wachs, Priscila; Lacerda, Daniel Pacheco; Saurin, Tarcisio Abreu (Brazilian Journal of Operations & Production Management, 2025)
Goal: This study examines the sustainability of Brazil’s soybean supply chain, highlighting deficiencies despite limited initiatives. It utilizes the Theory of Constraints (TOC), specifically the Current Reality Tree (CRT), to identify and address sustainability challenges. Design/Methodology/Approach: Eleven interviews with supply chain representatives were conducted to identify sustainability barriers. The CRT tool maps undesirable effects and root causes across environmental, social, and economic dimensions. Results: Economic sustainability exhibited the highest number of underlying causes, followed by environmental and social pillars. Key issues include strained inter-chain relationships impacting economic outcomes, the imperative for eco-friendly practices and technologies, and the importance of community and employee development. Additionally, eight leverage points for improvement, such as Defensive agricultural practices exceeding permitted levels, were identified, and their implications discussed. Practical implications: Insights suggest strategic interventions to enhance supply chain sustainability, emphasizing collaborative efforts, environmental stewardship, and human resource development. Addressing sustainability gaps could foster better socio-economic conditions within local communities and improve the overall industry reputation. Limitations of the investigation: The study’s scope is limited to the soybean supply chain in Brazil, potentially constraining generalizability. Future research could broaden the focus to include other agricultural sectors, global comparisons, or involve additional stakeholders to provide a more comprehensive perspective. Originality/Value: This research uniquely applies TOC’s CRT to analyze sustainability in a major agricultural supply chain, offering actionable insights and highlighting critical areas for improvement.